The worst of times: How life on earth survived eighty million years of extinctions - Wignall, Paul B. (New Jersey Princeton University press, 2015)
260 million years ago, life on Earth suffered wave after wave of cataclysmic extinctions, with the worst--the end-Permian extinction--wiping out nearly every species on the planet. This book delves into the mystery behind these extinctions and sheds light on the fateful role the primeval supercontinent, known as Pangea, may have played in causing these global catastrophes. Drawing on the latest discoveries as well as his own field expeditions to remote corners of the world, Paul Wignall reveals what scientists are only now beginning to understand about the most prolonged period of environmental crisis in Earth's history.